Trusted Data Transmission Using Data Scrambling Security Method with Asymmetric Key Algorithm for Synchronization - Saadah, Nihayatus; Astawa, I Gede Puja; Sudarsono, Amang (Politeknik Elektronika Negeri Surabaya (PENS), 2018)
Security is a major concern of the internet world because the development of the Internet requires the security of data transmission. The security method helps us to store valuable information and send it over an insecure network so that it can not be read by anyone except the intended recipient. Security algorithm uses data randomization method. This method of data information randomization has a low computation time with a large number of bits when compared to other encryption algorithms. In general, the encryption algorithm is used to encrypt data information, but in this research the encryption algorithm is used for synchronization between the sender and the intended recipient. Number of bits on asymmetric key algorithm for synchronization are the 64-bits, 512-bits and 1024-bits. We will prove that security methods can secure data sent with low computational time with large number of bits. In the result will be shown the value of computing time with variable number of bits sent. When data are sent by 50 bytes, encryption time required 2 ms using 1024 bits for synchronization technique asymmetric key algorithm.Â